"Don't Just Study our Distress, Do Something": Implementing and Evaluating a Modified Stepped-Care Model for Health Care Worker Mental Health During the COVID-19 Pandemic. (January 2023) - Sheehan, Kathleen A.; Schulz-Quach, Christian; Ruttan, Lesley A.; MacGillivray, Lindsey; McKay, Martha S.; Seto, Alison; Li, Adrienne; Stewart, Donna E.; Abbey, Susan E.; Berkhout, Suze G.
Objective: Throughout the COVID-19 pandemic, there have been concerns about the mental health of health care workers (HCW). Although numerous studies have investigated the level of distress among HCW, few studies have explored programs to improve their mental well-being. In this paper, we describe the implementation and evaluation of a program to support the mental health of HCW at University Health Network (UHN), Canada's largest healthcare network. Methods: Using a quality improvement approach, we conducted a needs assessment and then created and evaluated a modified stepped-care model to address HCW mental health during the pandemic. This included: online resources focused on psychoeducation and self-management, access to online support and psychotherapeutic groups, and self-referral for individual care from a psychologist or psychiatrist. We used ongoing mixed-methods evaluation, combining quantitative and qualitative analysis, to improve program quality. Results: The program is ongoing, running continuously throughout the pandemic. We present data up to November 30, 2021. There were over 12, 000 hits to the UHN's COVID mental health intranet web page, which included self-management resources and information on group support. One hundred and sixty-six people self-referred for individual psychological or psychiatric care. The mean wait time from referral to initial appointment was 5.4 days, with an average of seven appointments for each service user. The majority had moderate to severe symptoms of depression and anxiety at referral, with over 20% expressing thoughts of self-harm or suicide. Post-care user feedback, collected through self-report surveys and semistructured interviews, indicated that the program is effective and valued. Conclusions: Development of a high-quality internal mental health support for HCW program is feasible, effective, and highly valued. By using early and frequent feedback from multiple perspectives and stakeholders to address demand and implement changes responsively, the program was adjusted to meet HCW mental health needs as the pandemic evolved.